Boosting the Confidence of Novice Nurses as Patient Educators - Richard P. Becker (The Journal of Continuing Education in Nursing, 2026)
Patient education is a core nursing responsibility, but novice nurses are often intimidated by the prospect of performing this important task. New nurses can learn that they can indeed be effective patient educators through enjoyable, even fun, activities that offer them practical experience and lead to greater confidence.